Inflation Targeting Is a Success, So Far: 100 Years of Evidence from Swedish Wage Contracts - Lars Jonung; Klas Fregert (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
We evaluate the Swedish inflation targeting regime adopted in 1993-1995 using a novel approach based on a unique data set on the characteristics of collective wage agreements between 1908 and 2008. We find that the inflation targeting regime of 1995-2008 stands out as an exceptionally stable policy regime as judged by the willingness of wage contract-makers to repeatedly commit to three-year non-indexed wage agreements. Inflation targeting gained instant credibility in the sense that the labor market organizations entered long-term wage agreements at the same time as this new regime was announced. Inflation targeting has thus reduced macroeconomic uncertainty compared to previous regimes adopted in Sweden, including the gold standard before and after World War I, the price level targeting of the 1930s, the Bretton Woods period of fixed exchange rates. As judged by the reactions of the labor market participants, inflation targeting in Sweden is a successat least so far.
Keywords: E30; E42; E65; 330; Inflation targeting; policy regime; contract length; wage indexation; Lucas critique; Sweden; credibility; Inflation Targeting; Wirtschaftspolitische Wirkungsanalyse; Lohnbildung; Tarifpolitik; Lohnindexierung; Schweden